2016
DOI: 10.1515/med-2016-0054
|View full text |Cite
|
Sign up to set email alerts
|

Informed consent in robotic surgery: quality of information and patient perception

Abstract: AbstractIntroductionObtaining a valid informed consent in the medical and surgical field is a long debated issue in the literature. In robotic surgery we believe in the necessity to follow three arrangements to make the informed consent more complete.Material and methodsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…Even our only preemptive patient decided to delay the transplantation till the end of the lockdown, accepting the probability of starting dialysis treatment. The temporary suspension of elective living donor transplantation is supported by the most recent recommendations worldwide [ 5 , 15 , 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even our only preemptive patient decided to delay the transplantation till the end of the lockdown, accepting the probability of starting dialysis treatment. The temporary suspension of elective living donor transplantation is supported by the most recent recommendations worldwide [ 5 , 15 , 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the light of above mentioned, the information process is then essential [ 10 , 11 , 12 ]. Any person wishing to undergo a tattoo or piercing procedures should be exhaustively informed (including through written notice) about the process of said procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Our experience has showed that the presence of kidney vascular anomalies should not be considered a limit for kidney's transplantation. Therefore, kidneys with multiple renal arteries could be transplanted using the technique that best fits in each surgical situation according to the opinion of surgeons [61]. We consider that the success obtained with suboptimal kidney transplantation and with the associated physical activity allowed to extend the utilization of suboptimal kidneys.…”
Section: Discussionmentioning
confidence: 99%